2019
DOI: 10.1093/nar/gkz236
|View full text |Cite
|
Sign up to set email alerts
|

Mimivirus encodes a multifunctional primase with DNA/RNA polymerase, terminal transferase and translesion synthesis activities

Abstract: Acanthamoeba polyphaga mimivirus is an amoeba-infecting giant virus with over 1000 genes including several involved in DNA replication and repair. Here, we report the biochemical characterization of gene product 577 (gp577), a hypothetical protein (product of L537 gene) encoded by mimivirus. Sequence analysis and phylogeny suggested gp577 to be a primase-polymerase (PrimPol)—the first PrimPol to be identified in a nucleocytoplasmic large DNA virus (NCLDV). Recombinant gp577 protein purified as a homodimer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
(86 reference statements)
1
11
0
Order By: Relevance
“…2006 ). For the analysis, we have not considered the standalone primases, gp577 and gp857 as biochemical characterization showed that mimiviral gp577 is a primase-polymerase (PrimPol) that is involved in repair rather than replication and gp857 appears to be a paralog of gp577 ( Gupta et al. 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2006 ). For the analysis, we have not considered the standalone primases, gp577 and gp857 as biochemical characterization showed that mimiviral gp577 is a primase-polymerase (PrimPol) that is involved in repair rather than replication and gp857 appears to be a paralog of gp577 ( Gupta et al. 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the core replication proteins, namely, DNA polymerase (gp351), origin binding protein (gp1), primase-helicase bifunctional proteins (gp229), SSBP (gp544), sliding clamps (gp886, gp532, gp124), clamp loaders (gp549, gp538, gp513, gp425, gp441), ligase (gp331), RNase H (gp326, gp371), and topoisomerases (gp243, gp515, gp216), Mimivirus encodes several primases (gp577, gp857), helicases (gp612, gp132, and gp635), and bifunctional primase-helicase (gp8) proteins. Although their role in genome replication is not clear, it was recently shown that some of them, such as gp577, gp857, and gp8, do not appear to be involved in DNA replication ( Gupta et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…PrimPol is an important component to maintain adaptive DNA replication by repriming replication restart downstream of replication stalling lesions and structures ( 38 , 39 ). Understanding how cells adapt to genotoxic agents and how PrimPol mediates responses in replication fork restart has become increasingly important to optimize tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Primer extension studies were further conducted for N 2 ‐Bn‐dG with gp577, a viral PrimPol protein encoded by mimivirus employing different cofactors (magnesium and manganese metal ions), NTPs (nucleotide triphosphates) and dNTPs. [ 91 ] Bypass efficiency of gp577 was promoted by manganese (over magnesium), which compromises the fidelity of the enzyme across from N 2 ‐Bn‐dG adduct. [ 91 ]…”
Section: Tls Studies Of Specific N2‐dg Damaged Dnasmentioning
confidence: 99%
“…[ 91 ] Bypass efficiency of gp577 was promoted by manganese (over magnesium), which compromises the fidelity of the enzyme across from N 2 ‐Bn‐dG adduct. [ 91 ]…”
Section: Tls Studies Of Specific N2‐dg Damaged Dnasmentioning
confidence: 99%